Improving Listening Skill By using Audio-Lingual (ALM) For Students in The Grade 7th at SMP Dharma Patra Pangkalan susu - Anindya Nabila; Resa Kristianda; Muhammad Hasan; Supriadi (Journal of Classroom Action Research, 2023)
This research investigates the implementation of the Audio-lingual Method (ALM) to enhance listening skills among Junior High School students. The study used a classroom action research (CAR) approach, involving three cycles with observations, pre-tests, post-tests, and a questionnaire. The findings revealed that students initially struggle with listening in English due to limited vocabulary, grammatical difficulties, pronunciation issues, and a lack of confidence. The ALM significantly improved students' listening comprehension skills through audio recordings, dialogues, interactive activities, and authentic materials. Around 75% of students felt significantly assisted and found it easier to comprehend English vocabulary after the ALM implementation. However, 15% of students expressed disagreement, citing continued struggles with limited vocabulary. The ALM positively influences students' listening skills by combining listening practice with interactive activities and authentic materials. To further enhance students' listening abilities, teachers should address vocabulary limitations and pronunciation challenges, and employ additional strategies to foster a supportive and enjoyable learning environment. Future research should explore supplementary approaches and resources that complement the ALM to further enhance students' listening skills. Evaluating the long-term impact of the ALM on students' listening abilities would provide valuable insights into its effectiveness over an extended period. By implementing these findings, educators can effectively enhance students' listening skills and promote their overall English language proficiency. Keywords: Listening skills, Audio Lingual Method (ALM), effectiveness, classroom action research (CAR), observations.